2018
DOI: 10.1177/0020764018815207
|View full text |Cite
|
Sign up to set email alerts
|

Expressed emotion and socio-demographic and clinical factors in families of Brazilian patients with schizophrenia

Abstract: Background Family members are the main caregivers of people with schizophrenia in community-based mental health services. The literature emphasizes the family dynamic and Expressed Emotion (EE) of the family members as fundamental determinants in the course of this mental disorder

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…It is important to emphasize that the literature has greater knowledge about the effect of CC in the course of the disorder (Alvarez-Jimenez et al, 2012) and our finding can be related to a higher level of EOI in Brazilian culture (Martins et al, 1992;Zanetti et al, 2019). High levels of EOI in our context can be explained by the fact that Brazil is a developing country and, therefore, expectations regarding the future and patient productivity may be lower when compared to industrialized/developed countries, which may provide a lower level of criticism in detriment to the EOI (Martins et al, 1992).…”
Section: Effect Of Family Environment Over the Relapses After The First-episode Psychosismentioning
confidence: 67%
See 1 more Smart Citation
“…It is important to emphasize that the literature has greater knowledge about the effect of CC in the course of the disorder (Alvarez-Jimenez et al, 2012) and our finding can be related to a higher level of EOI in Brazilian culture (Martins et al, 1992;Zanetti et al, 2019). High levels of EOI in our context can be explained by the fact that Brazil is a developing country and, therefore, expectations regarding the future and patient productivity may be lower when compared to industrialized/developed countries, which may provide a lower level of criticism in detriment to the EOI (Martins et al, 1992).…”
Section: Effect Of Family Environment Over the Relapses After The First-episode Psychosismentioning
confidence: 67%
“…Inclusion criteria for family members were age of 18 years or older; to be referred as the main caregiver by the FEP patient; and living with the patient for at least 6 months. The duration criterion of living together with the patient was based on the clinical experience of the researchers with relatives of patients diagnosed with psychosis (Zanetti et al, 2019).…”
Section: Participantsmentioning
confidence: 99%
“…High criticism in families was associated in earlier studies with parents’ reduced self-blame ( 39 ) and causal attributions of disease to personal, internal, and controllable factors ( 40 , 41 ), overall caregiver burden and distress ( 39 , 42 44 ), and patients’ male gender ( 45 ), both higher ( 46 ) and lower ( 42 ) patients’ age, unemployment ( 47 ), longer duration of untreated psychosis ( 43 ), more previous hospitalizations ( 47 ) or psychotic episodes ( 48 ), better cognitive functioning ( 47 ), higher PC ( 44 , 49 , 50 ), patients’ disturbed/aggressive behavior ( 51 , 52 ), and higher depression/anxiety ( 47 ), but no other aspects of psychopathology (positive, negative symptoms) ( 39 , 43 , 53 ). We found that high criticism in families was significantly predicted by parents’ burden from their offspring’s aggressive behavior, corroborating previous findings, but also by outpatients ever being married, higher education, and history of suicide attempts (all three not previously reported).…”
Section: Discussionmentioning
confidence: 88%
“…High EOI in families was earlier associated with relatives’ female gender ( 46 , 51 , 54 , 55 ) but also male gender ( 42 ), unemployed status ( 55 ), higher caregiver burden and distress ( 39 , 42 44 ), causal attributions of disease to universal, external, and uncontrollable factors ( 40 , 41 ), less time spent with patient ( 42 ), and patients’ lower age ( 42 , 46 ), unemployment ( 46 ), more previous hospitalizations ( 55 ), higher depression/anxiety, lower aggression ( 54 ), and higher PC ( 44 ). In this study, high EOI in families was significantly predicted by parents’ female gender and higher burden (specifically regarding social life), corroborating previous findings, but also by higher parents’ age and outpatients’ female gender, not previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…O aumento dos níveis de EE e de seus componentes está associado ao aumento do número de recaídas e rehospitalizações em pacientes no PEP (ÁLVAREZ-JIMENEZ et al, 2012;BUTZLAFF;HOOLEY, 1998;BROWN, 1977). (KOUTRA et al, 2015;ZANETTI et al, 2018a). Em relação aos familiares, o grau de parentesco, sexo, e variáveis como sobrecarga de cuidado, níveis de estresse percebido, estratégias de enfrentamento utilizadas para lidar com a doença e atribuição negativa à sintomatologia do paciente também foram associados a maiores taxas de EE (COTTON et al, 2013;RAUNE;KUIPERS;BEBBINGTON, 2004;ZANETTI et al, 2018a, ZANETTI et al, 2018b.…”
Section: Introductionunclassified